Pengaruh serai (Cymbopogon citratus) terhadap profil darah dan kadar asam urat pada tikus - Aryani Satyaningtijas; Faisal Anthony; Muhammad Naufal Febrian Jamaludin; Anggara Widyawiratma; Muhammad Joserisal Alghifarry Pakkawaru; Damiana Rita Ekastuti; Kusdiantoro Mohamad; Mawar Subangkit; Aprilia Hardiati (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Lemongrass (Cymbopogon citratus) is a medicinal plant with antioxidant and antimicrobial properties. This study evaluated the effects of 20% and 80% lemongrass infusion on haematological profiles and uric acid levels in Sprague Dawley rats. Thirty rats were assigned to three groups: control, 20% infusion, and 80% infusion groups. The results showed no significant differences (P>0.05) in haematological parameters, although fluctuations in erythrocyte and leukocyte indices occurred. The 80% infusion reduced erythrocyte parameters, suggesting potential hypochromic macrocytic anaemia, while the 20% infusion reduced leukocyte counts and uric acid levels. These findings indicate that lemongrass infusion has immunomodulatory and anti-hyperuricemic effects, although higher concentrations may affect erythrocytes.